2016
DOI: 10.1590/1518-8345.1054.2777
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the usability of a digital learning technology prototype for monitoring intracranial pressure

Abstract: Objective: to assess the usability of a digital learning technology prototype as a new method for minimally invasive monitoring of intracranial pressure. Method: descriptive study using a quantitative approach on assessing the usability of a prototype based on Nielsen's ten heuristics. Four experts in the area of Human-Computer interaction participated in the study. Results: the evaluation delivered eight violated heuristics and 31 usability problems in the 32 screens of the prototype. Conclusion: the suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
(80 reference statements)
0
4
0
3
Order By: Relevance
“…These results underpin the importance of submitting a new technology developed for assessment by specialists in the area of interest and technological development, to avoid making it directly available to the target audience, before correcting possible flaws that would result in less adherence to the use of the tool (18) . The validation of a new web software allows the inserted resources to be optimized and better applied, to guarantee the suitable function of disseminating relevant information to the users who access it (19) . Thus, when reaching high standards of agreement among experts in the field of aging, the ability of this tool to provide diagnostic tools and specific interventions directed to the weaknesses identified by workers at the time of access is observed.…”
Section: Discussionmentioning
confidence: 99%
“…These results underpin the importance of submitting a new technology developed for assessment by specialists in the area of interest and technological development, to avoid making it directly available to the target audience, before correcting possible flaws that would result in less adherence to the use of the tool (18) . The validation of a new web software allows the inserted resources to be optimized and better applied, to guarantee the suitable function of disseminating relevant information to the users who access it (19) . Thus, when reaching high standards of agreement among experts in the field of aging, the ability of this tool to provide diagnostic tools and specific interventions directed to the weaknesses identified by workers at the time of access is observed.…”
Section: Discussionmentioning
confidence: 99%
“…Manzoor et al [40] found that 100% of the utilized sample of university websites suffered from broken links (H5), while this percentage remained also high (87.23%) for museum websites. Carvalho et al (2016) [41] highlighted the importance of embedding a breadcrumb at the top of the screen to track user's actions and show their exact location, as well as the way to get there, however, in the sample of anatomy museums only 50% had this integrated feature (H6). Moreover, a sitemap (H7) functionality was present in only 22.52% of the museums' websites, while in the Manzoor et al [40] survey it is recorded that only 30% of university websites in Europe, less in Canada (25%) and even less in USA (20%) involved this key property.…”
Section: Discussionmentioning
confidence: 99%
“…Podemos citar a avaliação heurística e dentre elas, pode-se citar as heurísticas de Nielsen. Buscou-se seguir os passos sugeridos por ele, como o menu em que profissional terá a liberdade de escolher o local que iniciará, o check list que se assemelha ao cotidiano impresso do usuário além de garantir que o formato de check list se repete em todos os domínios, favorecendo a consistência de padrões (14) . E ao finalizar o passo a passo do domínio quando algum cuidado não foi checado, aparecerá uma mensagem -feedback-informando que o profissional estará correndo algum risco relacionado a segurança do paciente.…”
Section: Implicações à Prática Profissionalunclassified
“…O feedback é também um item elementar que favorece a avaliação da usabilidade, acrescido da estética e design minimalista com títulos curtos, contribuindo para adesão ao uso do aplicativo (14) . Para melhorar os recursos da tecnologia, há também um ícone "Capacitação" que levará a uma tela que será desenvolvida futuramente com links de artigos científicos sobre o tema MPP e atividades interativas que possibilitem o profissional a atualizar-se e capacitar-se sobre o tema, proporcionando maior segurança nas suas ações.…”
Section: Implicações à Prática Profissionalunclassified